Pelatihan Positive Self Talk untuk Meningkatkan Motivasi Siswa Belajar di Sekolah - Chaizuran, Meutia (FKM UIN Sumatera Utara Medan, 2023)
Learning motivation is one of those things that students must have to support the learning process well. Pandemic which has been going on since 2019 required students to learn online and get help from parents in learning. When the normal system is applied again, the students lack of confidence in learning process and doing the task independently. Based on this problem, this community service activity is carried out to improve the student motivation in schools by changing their irrational thinking and turning it into rational thinking through positive self-talk. The method of community service activity begins with data collection through interviews and observations, then conducting analysis of needs, implementing stages, and evaluation. This activity takes well place and students know the simple way that can be done to increase student in learning motivation.